Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-17102-w
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen Receptor-α binds the FOXP3 promoter and modulates regulatory T-cell function in human cervical cancer

Abstract: Oestrogen controls Foxp3 expression in regulatory T cells (Treg cells) via a mechanism thought to involve oestrogen receptor alpha (ERα), but the molecular basis and functional impact of ERα signalling in Treg cells remain unclear. We report that ERα ligand oestradiol (E2) is significantly increased in human cervical cancer (CxCa) tissues and tumour-infiltrating Treg cells (CD4+CD25hiCD127low), whereas blocking ERα with the antagonist ICI 182,780 abolishes FOXP3 expression and impairs the function of CxCa infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 73 publications
1
45
0
1
Order By: Relevance
“…in the population of Tregs. Of interest, the estrogen signalling pathway was robustly upregulated in these cells consistent with previous data demonstrating that ER-alpha binds the FOXP3 gene promoter driving Tregs expansion and anti-inflammatory function [45,139]. As previously stated (see Section 6.1), we and others have highlighted a cross-talk between LRH-1/NR5A2 and ER-alpha that intimately cooperate to activate common target genes suggesting a role of LRH-1/NR5A2 in promoting the expansion of the Tregs population through a potential interaction with the FOXP3 gene promoter [94][95][96].…”
Section: The Anti-diabetic Benefits Of the Bl001/lrh-1/nr5a2 Signallisupporting
confidence: 87%
“…in the population of Tregs. Of interest, the estrogen signalling pathway was robustly upregulated in these cells consistent with previous data demonstrating that ER-alpha binds the FOXP3 gene promoter driving Tregs expansion and anti-inflammatory function [45,139]. As previously stated (see Section 6.1), we and others have highlighted a cross-talk between LRH-1/NR5A2 and ER-alpha that intimately cooperate to activate common target genes suggesting a role of LRH-1/NR5A2 in promoting the expansion of the Tregs population through a potential interaction with the FOXP3 gene promoter [94][95][96].…”
Section: The Anti-diabetic Benefits Of the Bl001/lrh-1/nr5a2 Signallisupporting
confidence: 87%
“…In cervical cancer, FOXP3 levels were reduced and suppressive function of Tregs was minimized in the presence of an ERα antagonist. These studies also found a complex of ERα, E2 and FOXP3 as well as ERα occupancy at the FOXP3 promoter (152). These data suggest that estrogenic signaling directly regulates Treg suppressive function through FOXP3.…”
Section: Estrogen Regulates Pro-tumor Infiltrating Lymphocytesmentioning
confidence: 60%
“…Estradiol is the most important steroid hormone in the normal female endocrine system (44); the present study identified that endogenous estradiol levels in patients with cervical cancer were higher compared with controls, which suggests that high endogenous estradiol levels are associated with an elevated risk of cervical cancer. Estrogen receptor-α binds to the forkhead box P3 promoter and modulates regulatory T-cell function in human cervical cancer (45). Therefore, sex hormones may have an influence on the immune system.…”
Section: Discussionmentioning
confidence: 99%